Elevated salicylic acid levels conferred by increased expression of ISOCHORISMATE SYNTHASE 1 contribute to hyperaccumulation of SUMO1 conjugates in the Arabidopsis mutant early in short days 4. (23rd June 2014) - Villajuana‐Bonequi, Mitzi; Elrouby, Nabil; Nordström, Karl; Griebel, Thomas; Bachmair, Andreas; Coupland, George
Summary Post‐translational modification of proteins by attachment of small ubiquitin‐like modifier (SUMO) is essential for plant growth and development. Mutations in the SUMO protease early in short days 4 (ESD4) cause hyperaccumulation of conjugates formed between SUMO and its substrates, and phenotypically are associated with extreme early flowering and impaired growth. We performed a suppressor mutagenesis screen of esd4 and identified a series of mutants called suppressor of esd4 (sed), which delay flowering, enhance growth and reduce hyperaccumulation of SUMO conjugates. Genetic mapping and genome sequencing indicated that one of these mutations (sed111) is in the gene salicylic acid induction‐deficient 2 (SID2), which encodes ISOCHORISMATE SYNTHASE I, an enzyme required for biosynthesis of salicylic acid (SA). Analyses showed that compared with wild‐type plants, esd4 contains higher levels of SID2 mRNA and about threefold more SA, whereas sed111 contains lower SA levels. Other sed mutants also contain lower SA levels but are not mutant for SID2, although most reduce SID2 mRNA levels. Therefore, higher SA levels contribute to the small size, early flowering and elevated SUMO conjugate levels of esd4. Our results support previous data indicating that SUMO homeostasis influences SA biosynthesis in wild‐type plants, and also demonstrate that elevated levels of SA strongly increase the abundance of SUMO conjugates.